Reflections on developing a hospital-wide health care transition program - Ellen Iverson; Caitlin S. Sayegh; Courtney Porter; Diane Tanaka; Roberta Williams (Health Care Transitions)
Background: Despite the importance of an organized, planned transition to adult healthcare for adolescents with chronic health conditions, pediatric hospitals have struggled to adequately support this process. Particularly over the past two decades, pediatric hospitals have taken different tactics in their efforts to provide systematic transition support and faced unique challenges developing comprehensive, sustainable programs. Objective: The purpose of this article is to reflect on the experience of building transition services through the 2010s decade at a large quaternary pediatric hospital, Children's Hospital Los Angeles (CHLA), which serves a diverse and largely socioeconomically disadvantaged population. Results: At CHLA, hospital-wide efforts began with informal gatherings of advocates who championed transition support. This led to collaboration and pooling of resources to develop a collective approach to transition. CHLA’s transition efforts matured over the 2010’s decade, coinciding with national advances in transition frameworks and transition-focused research. Ultimately, CHLA received a large philanthropic gift which provided resources to expand transition support throughout the institution by creating a cross-disciplinary, formalized program and infrastructure designed to support all adolescents to successfully transition to adult healthcare. Conclusion: This article archives CHLA’s unique path toward developing hospital-wide transition services and lessons learned during these efforts may be informative to others striving to improve transition services.